Lactococcus Lactis Strain A5 Producing Nisin-like Bacteriocin Active against Gram Positive and Negative Bacteria - Nur Shazana Azhar; Noor Hasniza Md Zin; Tengku Haziyamin Tengku Abdul Hamid (Tropical Life Sciences Research, 2017)
In this study, a Lactic acid bacteria (LAB) strain was isolated on MRS medium from gastro-intestinal tissues of Broadhead catfish (Clarias macrocephalus). Out of 50 isolates, 25 isolates were found to be positive on lactose utilization test and was identified to be Gram positive cocci. Using disc diffusion methods, one out of 22 isolates, i.e., a strain A5 demonstrated inhibitions against three indicator organisms; Bacillus cereus, Staphylococcus aureus and Salmonella thyphimurium. Partial 16S rDNA sequencing identified isolate A5 as a member of Lactococcus lactis, with 100% DNA homology. Cell free supernatant fluid from Lactococcus lactis A5 showed inhibitory activities against both gram positive pathogens (Bacillus cereus and Staphylococcus aureus) and gram negative pathogens (Salmonella thyphimurium). Chloroform precipitated bacteriocin retained antagonistic activities in the presence of catalase and lysozyme; and was completely inactivated by Proteinase K treatment. The bacteriocin has a molecular weight of 3.4 kDa, based on SDS-PAGE analysis and the extract was heat stable at 37°C and 65°C, for 15 minutes. The antibacterial activity was suppressed with the addition of EDTA but was significantly increased with the addition of SDS, Triton X-100, Tween 20 and Tween 80. This bacteriocin belongs to class 1 bacteriocin, which was shown to have a nisin-like properties. This strain can be used as potential probiotics in animal or aquaculture feeding; and the bacteriocin it produces will be useful in food preservative. Dalam kajian ini, strain bakteria asid Laktik (LAB) telah diasingkan pada medium MRS daripada tisu gastro-intestinal ikan keli Broadhead (Clarias macrocephalus). Daripada 50 isolat, 25 isolat didapati positif pada ujian penggunaan laktosa dan dikenal pasti sebagai cocci gram positif. Dengan menggunakan kaedah penyebaran cakera, satu daripada 22 isolat, iaitu, strain A5 menunjukkan hambatan terhadap tiga organisma penunjuk; Bacillus cereus, Staphylococcus aureus dan Salmonella thyphimurium. Susunan seksyen 16S rDNA dikenal pasti mengasingkan A5 sebagai ahli Lactococcus lactis, dengan 100% homologi DNA. Cecair supernatan bebas dari Lactococcus lactis A5 menunjukkan aktiviti perencatan terhadap kedua-dua patogen positif gram (Bacillus cereus dan Staphylococcus aureus) dan gram negatif patogen (Salmonella thyphimurium). Chloroform precipitated bacteriocin mengekalkan aktiviti antagonistik di hadapan katalase dan lysozyme; Dan benar-benar tidak aktif oleh rawatan Proteinase K. Bacteriocin mempunyai berat molekul 3.4 kDa, berdasarkan analisis SDS-PAGE dan ekstrak adalah haba stabil pada 37 °C dan 65 °C, selama 15 minit. Aktiviti antibakteria ditekan dengan penambahan EDTA tetapi meningkat dengan ketara dengan penambahan SDS, Triton X-100, Tween 20 dan Tween 80. Bacteriosin ini tergolong dalam kelas 1 bacteriocin, yang ditunjukkan mempunyai sifat seperti nisin. Strain ini boleh digunakan sebagai probiotik yang berpotensi dalam pemakanan haiwan atau akuakultur; dan bacteriosin yang dihasilkan akan berguna dalam pengawet makanan.